The Influence of Islamic Religious ‎Education Learning on the ‎Formation of Religious Character - Fitman ‎; Riyan Maulana (CV Naskah Aceh, 2025)
This study aims to determine: 1) Learning Islamic religious education in the 8th grade of ‎SMP Muhammadiyah Simpang Empat, 2) The formation of religious character in 8th ‎grade students at SMP Muhammadiyah Simpang Empat, and 3) The influence of ‎Islamic religious education learning on the formation of religious character in 8th grade ‎students at SMP Muhammadiyah Simpang Empat for the 2019/2020 school year. This ‎research uses a quantitative approach and descriptive research type. The population in ‎this study were students of grade 8, amounting to 139 people with the sample used as ‎many as 46 people. The data collection tools use questionnaires, observations, and ‎documentation. The previous questionnaire was tried out and tested for validity and ‎reliability testing. The data analysis technique used the product moment correlation and ‎the coefficient of determination. The research results can be concluded as follows: 1) ‎Learning Islamic religious education in the 8th grade of SMP Muhammadiyah Simpang ‎Empat is included in the “low” category with an average score of 35.20, 2) The ‎formation of religious character in 8th grade students at SMP Muhammadiyah Simpang ‎Empat is included in the “medium” category with an average score of 42.24, and 3) ‎There is significant influence between learning Islamic religious education on the ‎formation of religious character in 8th grade students at SMP Muhammadiyah Simpang ‎Empat for the 2019/2020 school year. This is proven by the calculation of rcount of ‎‎0.850. At a significance level of 5% or α= 0.05, the r table value is 0.297. Because the ‎value of rcount ≥ rtable is 0.850 ≥ 0.297, so Ho is rejected and Ha is accepted which ‎says there is a significant influence between learning Islamic religious education on the ‎formation of religious character in 8th grade students at SMP Muhammadiyah Simpang ‎Empat.‎